2017
DOI: 10.1007/s00424-017-2067-y
|View full text |Cite
|
Sign up to set email alerts
|

Surface-modified CMOS IC electrochemical sensor array targeting single chromaffin cells for highly parallel amperometry measurements

Abstract: Amperometry is a powerful method to record quantal release events from chromaffin cells and is widely used to assess how specific drugs modify quantal size, kinetics of release, and early fusion pore properties. Surface-modified CMOS-based electrochemical sensor arrays allow simultaneous recordings from multiple cells. A reliable, low-cost technique is presented here for efficient targeting of single cells specifically to the electrode sites. An SU-8 microwell structure is patterned on the chip surface to prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(35 citation statements)
references
References 50 publications
1
34
0
Order By: Relevance
“…The tip of the carbon fiber was entirely coated with wax and then cut such that only the circular area at the end of the cut fiber was exposed as the working electrode. The area of such a CFM is similar to that of onchip electrodes after post-fabrication [11], [13], which also will be fabricated in the future on the FSCV chip described here. The CFM was immersed into a petri dish filled with a buffer solution containing 140 mM NaCl, 5 mM KCl, 5 mM CaCl 2 , 1 mM MgCl 2 , and 10 mM HEPES/NaOH pH 7.3.…”
Section: Measurement Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The tip of the carbon fiber was entirely coated with wax and then cut such that only the circular area at the end of the cut fiber was exposed as the working electrode. The area of such a CFM is similar to that of onchip electrodes after post-fabrication [11], [13], which also will be fabricated in the future on the FSCV chip described here. The CFM was immersed into a petri dish filled with a buffer solution containing 140 mM NaCl, 5 mM KCl, 5 mM CaCl 2 , 1 mM MgCl 2 , and 10 mM HEPES/NaOH pH 7.3.…”
Section: Measurement Resultsmentioning
confidence: 99%
“…The detector array provides a five-fold increase in temporal resolution over the unidirectional-current detector array we reported previously in [11], [13]. …”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Using an array of 100 amperometric amplifiers in a CMOS device, the neurotransmitter release from chromaffin cells were recorded [6], [7].…”
Section: Introductionmentioning
confidence: 99%
“…Even if it is possible to use conventional carbon fiber ultramicroelectrodes to record exocytosis events, microfabrication techniques have significantly improved electrochemical sensing, particularly arrays of sensors [ 11 ]. For example, recent reviews have demonstrated that it is possible to record not only electrical cellular activity [ 12 ], but also to sense exocytosis events on conventional microelectrode arrays (MEA) [ 13 , 14 ]. Therefore, MEA may be used in basic research or clinical diagnostics for cell analysis–based drug discovery or environmental monitoring, where they help to monitor in-situ (in Petri dishes) not only cell functions via neurotransmitters release, but also enzymatic activity or cells respiratory activity (glucose consumption, lactate production), using electrochemical reactions on sensing electrodes [ 15 ].…”
Section: Introductionmentioning
confidence: 99%